The Expression of Galanin in the Parafacial Respiratory Group and its Effects on Respiration in Neonatal Rats. (1st August 2018) - Bautista, Tara G.; Fong, Angelina Y.; Pilowsky, Paul M.; Ikeda, Keiko; Kawakami, Kiyoshi; Spirovski, Darko; Onimaru, Hiroshi
Highlights: Expression of the inhibitory peptide galanin was confirmed in the parafacial respiratory group in neonatal rats. Expression of galanin was shown in intrinsically CO2 -sensitive Pre-Inspiratory neurons in the region. In rat brainstem-spinal cord preparations, bath application of galanin converted episodic breathing into single breaths. It also slowed breathing in those single breaths at baseline. Each breathing episode was found to be associated with a single, prolonged burst in Pre-Inspiratory neurons. Abstract: The inhibitory peptide galanin is expressed within the retrotrapezoidal nucleus (RTN) – a key central chemoreceptor site that also contains the active expiratory oscillator. It was previously reported that microinjection of galanin into pre-Bötzinger complex – containing the inspiratory oscillator – exerts inhibitory effects on inspiratory motor output and respiratory rhythm. In neonatal rats, the present study aimed to investigate: (1) expression of galanin within the parafacial respiratory group (pFRG), which overlaps anatomically and functionally with the adult RTN, and; (2) effects of galanin on respiratory rhythm using the in vitro brainstem-spinal cord preparation. We showed that 14 ± 2% of Phox2b-immunoreactive (ir) neurons in the parafacial region were also galanin-ir. Galanin peptide expression was confirmed within 3/9 CO2 -sensitive, Phox2b-ir Pre-Inspiratory neurons (Pre-I) recorded in parafacial region. Bath application of galanin (0.1–0.2 µM): (1) decreased the duration of membrane depolarization in both Pre-I and inspiratory pFRG neurons, and; (2) decreased the number of C4 bursts that were associated with each burst in Pre-I neurons within the pFRG. In preparations showing episodic breathing at baseline, the respiratory patterning reverted to the 'normal' pattern of single, uniformly rhythmic C4 bursts ( n  = 10). In preparations with normal respiratory patterning at baseline, slowing of C4 rhythm ( n  = 7) resulted although rhythmic bursting in recorded Pre-I neurons remained unperturbed ( n  = 6). This study therefore demonstrates that galanin is expressed within the pFRG of neonatal rats, including neurons that are intrinsically chemosensitive. Overall the peptide has an inhibitory effect on inspiratory motor output, as previously shown in adults.